The Potential Benefits of Dance Movement Therapy in Improving Couple Relations of Individuals Diagnosed With Autism Spectrum Disorder—A Review - Shuper Engelhard, Einat; Vulcan, Maya (Frontiers in Psychology, 2021)
A review of current literature indicates that adults diagnosed with autism spectrum disorder (ASD) feel the need for intimate and sexual relationships and maintain such relationships, despite and alongside their difficulties in emotional communication, social interactions, reciprocity, and verbal and non-verbal expression. This understanding calls for the development of intervention programs designed to support the specific needs and address the problems of couples where one partner is diagnosed with ASD. In view of the relevance and significant part played by body and movement in emotional development and psychotherapy, the present article offers a review of studies examining the contribution of dance movement therapy to both the quality of life and functioning of adults with ASD and therapeutic processes in couple therapy. This review aims to establish an infrastructure for the construction of intervention programs and for future studies designed to enhance the quality of life and independence of adults with ASD.